2010
DOI: 10.1007/s00109-010-0643-0
|View full text |Cite
|
Sign up to set email alerts
|

MIR152, MIR200B, and MIR338, human positional and functional neuroblastoma candidates, are involved in neuroblast differentiation and apoptosis

Abstract: MicroRNAs (MIRs) perform critical regulatory functions within cell networks, both in physiology as well as in pathology. Through the positional gene candidate approach, we have identified three MIRs (MIR152, MIR200B, and MIR338) that are located in regions frequently altered in neuroblastoma (NB) and target mRNAs encoding proteins involved in cell proliferation, neuroblast differentiation, neuroblast migration, and apoptosis. Expression analysis in NB biopsies and NB cell lines showed that these MIRs are dysre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…For example, it is down-regulated in endometrial serous adenocarcinoma (30), and HBV-related HCC (31). However, it is overexpressed in neuroblastoma (19). Therefore, conclusions regarding whether miR-152 and miR148a function as tumor suppressors have been controversial.…”
Section: Mir-152 and Mir-148a Have No Effect On Invasion Of Skov3 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is down-regulated in endometrial serous adenocarcinoma (30), and HBV-related HCC (31). However, it is overexpressed in neuroblastoma (19). Therefore, conclusions regarding whether miR-152 and miR148a function as tumor suppressors have been controversial.…”
Section: Mir-152 and Mir-148a Have No Effect On Invasion Of Skov3 Cellsmentioning
confidence: 99%
“…Our previous studies have shown that miR-152 and miR148a are down-regulated in gastric cancer, when compared to their matched non-tumor adjacent tissues (NATs) (18). In neuroblastoma, miR-152 is involved in cell proliferation, neuroblast differentiation, migration, and apoptosis (19). Here, we present data showing that the expression of miR-152 and miR-148a were down-regulated in ovarian cancer tissues compared to normal ovarian tissues, although the decreased expression of miR-148a was not statistically significant.…”
Section: Introductionmentioning
confidence: 99%
“…In those studies, the inhibition of miR-152 was observed to cause a decrease in cell growth in Hela cells. In neuroblastoma samples, the expression of miR-152 was upregulated, and miR-152 negatively controlled apoptosis by downregulating pro-apoptotic genes such as conserved helix-loop-helix ubiquitous kinase, cullin 5 and growth arrest and DNA-damage-inducible, alpha (37). By contrast, Zhou et al (9) reported that cell proliferation was remarkably inhibited by overexpression of miR-152 in ovarian cancer cells using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay.…”
Section: Mir-152 and Its Targets Are Associated With Cell Proliferatimentioning
confidence: 99%
“…Besides these abnormalities, gain of chromosomes 4q, 6p, 7q, 11q and 18q, amplification of MDM2 and MYC genes, and LOH at 14q, 10q, 19q13 have also been described [3, 4]. More recently, the involvement of miRNAs in neuroblastoma pathogenesis has been assessed [5, 6]. Deregulation of miRNAs expression in malignant neuroblastomas may be due to several factors, as MYCN amplification, chromosomal deletions, or abnormal epigenetic regulation [7].…”
Section: Introductionmentioning
confidence: 99%